Topological interface states in acoustic metamaterials - Milan Cajic (Proceedings, 8th International Congress of the Serbian Society of Mechanics, Kragujevac, Serbia, June 28-30, 2021)
This paper studies the topological interface modes at the interface of one-dimensional acoustic metamaterial chain in different unit cell configurations. The chain is composed of two sublattices that are inverted copies of each other and connected at the interface. The corresponding governing equations for the bulk band and frequency response function and eigenvalues of the finite chain are given and solved. The obtained results reveal the existence of interface modes within the bandgaps, showing the potential of the presented system to create sub-wavelength interface modes. The effect of stronger stiffness at the interface will be presented to show its influence on interface modes.